Restoring Tibial Slope and Sagittal Alignment of the Femoral Component in Unrestricted Kinematically Aligned Total Knee Arthroplasty Using Conventional versus Patient-Specific Instrumentation - Sadoghi, Patrick; Draschl, Alexander; Leitner, Lukas; Fischerauer, Stefan; Koutp, Amir; Clar, Clemens; Leithner, Andreas; Klasan, Antonio (The Journal of Knee Surgery, 2023)
Restoring sagittal alignment in kinematically aligned (KA) total knee arthroplasty (TKA) is crucial to avoid patellofemoral joint instability or overstuffing and to restore an adequate range of motion. This prospective study compared the accuracy of conventional instrumentation (CI) versus patient-specific instrumentation (PSI) in restoring sagittal alignment of KA TKA measured by the tibial slope and degree of flexion of the femoral component to the sagittal femoral axis. One hundred patients were randomized to receive either CI (n = 50) or PSI (n = 50) for KA TKA. Two observers measured pre- and postoperative X-rays to assess restoration of the tibial slope and sagittal flexion. Inter- and intraclass correlations were calculated, and postoperative tibial and femoral components were compared with preoperative anatomy. In 50 CI patients, 86% (n = 43) had the tibial slope restored exactly, and no deviation more than 1 degree was found. Deviations of 0 to 1 degree were detected in 14% (n = 7). In 50 patients of the PSI group, 56% (n = 28) achieved an exact anatomic tibial slope restoration and 20% (n = 10) showed a deviation more than 2 degrees compared with the preoperative measurement. Deviations ranging between 0 to 1 and 1 to 2 degrees were found in 22% (n = 11) and 2% (n = 1) of cases, respectively. Sagittal alignment of the femoral component showed in both groups no deviation exceeding 1 degree. The restoration of sagittal alignment in KA TKA was statistically significantly differently distributed between CI and PSI (p = < 0.001) without clinical relevance. We found that PSI increased the odds for deviations >2 degrees in tibial slope reconstructions from 0 to 0.20 ([95% confidence interval: 0.09–0.31]; p = 0.001). Both CI and PSI revealed adequate results with respect to restoring sagittal alignment of the tibial and femoral components in KA TKA. The conventional technique requires adequate adjustment of the intramedullary rod to avoid hyperflexion of the femoral component and attention must be paid when restoring the tibial slope using PSI. This is a prospective Level II study.
Keywords: kinematic alignment; total knee arthroplasty; patient-specific instrumentation; conventional instrumentation; sagittal alignment; posterior tibial slope; femoral flexion